Consumers’ purchase intention towards organic foods: a study among UiTM lecturers in northern region, Malaysia / Siti Meriam Ali ...[et al.] - Ali, Siti Meriam; Harun, Etty Harniza; Abdul Jalil, Muna; Mohamed Salleh, Musdiana (Institute of Research Management & Innovation (IRMI), 2011)
This study attempted to gain knowledge about consumer attitude towards organic food products. With sample of 136 respondents consist of lecturers from Universiti Teknologi MARA (Northern Zone). The data obtained from the survey were analyzed with chi- square test, ANOVA, and correlation analysis. Result from this study indicated that academician do aware of what is happening to surroundings with regards to environmental problems or ecological concern. The findings indicated that healthy consciousness factor have more impact on customer purchase intention of organic food products rather than environmental concern. Environmental concern was found to have less impact because academician perceive that although they have a knowledge toward environmental and ecological factors that can contribute to sustainable environment, however their current consumption pattern will not change their perception towards organic food product however good it is. Hence, this study is expected to provide understanding the reasons of buying and would probably help marketers of organic food products to establish a proper communication message to different category of buyers who exhibit their interest tow ards organic food products. The limitation of this study is that the sample was restricted to a single geographic area in Malaysia. Future research should focus on extended scope to all stated in Malaysia and further investigate the details of how consumer perceived the organic food products as a way for building sustainable consumption pattern.